Diagnosis of gastric cancer. Issue 5972 (21st June 1975) - Segal, A W; Healy, M J; COX, A G; Williams, I; Slavin, G; Smithers, A; Levi, A J
Abstract : A prospective comparison was made of the accuracy of different diagnostic methods for gastric cancer. The basis of the study was a consecutive series of 113 patients thought to have gastric pathology; cancer was the final diagnosis in 32. Endoscopy and radiology were the most accurate investigations, whereas biopsy, cytology, and clinical examination gave disappointing results. A wide range of clinical features and laboratory investigations were studied in all patients in an attempt to identify criteria suggestive of malignancy. Multifactorial computer analysis of these investigations failed to improve upon the radiological diagnosis. A systemic approach designed to make optimal use of limited endoscopic and histopathological resources in the diagnosis of gastric lesions is presented.